Formulation Sunscreen Spray Gel of Vetiveria zizanioides (L.) Nash Root Infusion - Damarwati, Vella Lailli; Fajarani, Rizky Anita; Sabeta, Meilidya Vani; Kurniawan, Muhammad Fariez; Winanta, Aji (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Vetiveria zizanioides (L.) Nash is one of the plants with high flavonoid compound content with antioxidant activity. This study aims to formulate a spray gel of the root of Vetiveria zizanioides (L.) Nash infusion determines UV protection and observes the level of irritation caused by the application.  This study used formulas at variations concentrations FI 1%, FII 5%, and FIII 10%. The formulas observed flavonoid content, sun protection factor (SPF) value, and irritation index. Flavonoid content was tested using the Willstatter method. The SPF value was determined in vitro using UV-spectrophotometer, while the irritation test was conducted using the Draize test method. The SPF value test results showed that Formula 0 (F0), FI, FII, FIII, and the commercial preparation had SPF values of 0.355, 2.856, 5.324, 6.634, and 13.438, respectively. Meanwhile, the irritation test obtained an irritation infection of 0.3 in the commercial preparation and 0.6 in F3. Therefore, FII has the potential to be UV-protected and have a minimal irritating effect.